2022
DOI: 10.1051/epjconf/202226901040
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on the fluid flow mixing process in agitated vessel

Abstract: The fluid mixing process is a common supportive phenomenon that often occurs in a large number of industrial systems. This phenomenon is the subject of many numerical and experimental analysis. The mixing process effectiveness depends on: mixing tank construction, mixing phases viscosity, temperature, density of liquids and, what is crucial, the impeller shape. The optimal design of impeller geometry is still an open issue. In this research work, the main objective is experimental investigations of the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The of PIV measurement described in detail in the paper Młynarczykowska et all. [12] In the final step of experimental analysis based on the results two keys criteria numbers were evaluated: Power number Np and Reynolds number Re. Those parameters designated according to the equations:…”
Section: Experimental Set-up and Methodologymentioning
confidence: 99%
“…The of PIV measurement described in detail in the paper Młynarczykowska et all. [12] In the final step of experimental analysis based on the results two keys criteria numbers were evaluated: Power number Np and Reynolds number Re. Those parameters designated according to the equations:…”
Section: Experimental Set-up and Methodologymentioning
confidence: 99%
“…The simulation results showed that flow pattern and dimensionless velocity distribution are related to Reynolds number and regime type without change values in the turbulent regime. The lowest drop of total power number for single and parallel configuration of the impellers was observed in laminar regime [5,6,78,79,164]. A large number of researchers have performed numerical simulations to examine the impact of impeller geometry on the mixing process in order to find optimal configuration, low mixing time or low power consumption [165][166][167].…”
Section: The Effect Of Impellersmentioning
confidence: 99%
“…the internal vessel geometry or configuration (baffles, coils, vessel bottom type, etc. [3][4][5][6]); -the fluid properties (densities, number of phases, a viscosity [7]);…”
Section: Introductionmentioning
confidence: 99%